Radicals in the Globalization Debate (Global Journal of Management and Business Research, 2020)
In this study, it is possible to define globalization by using a generally accepted approach, since Nakis will leave the phenomenon of globalization in many aspects. Globalization can be explained by technological developments which have economic, social, cultural, ecological and social dimensions and which are the driving force of them. Although the word origin dates back four hundred years when taken up with the historical process of globalization, it came to light in the 1960s and became a subject of much debate with the 80s.
Keywords: globalization; radicals; skeptics; transformers; technology; international firms; economy